Jaundice-predominant manifestation of Kawasaki disease in children - Huang, Ya-Ning; Lin, Chien-Yu; Chi, Hsin; Chiu, Nan-Chang; Huang, Daniel Tsung-Ning; Chang, Lung; Kung, Yen-Hsin; Huang, Ching-Ying (Frontiers in Pediatrics, 2024)
Background A jaundice-predominant presentation of Kawasaki disease (KD) is atypical. Methods A total of 12 children with KD with a predominant manifestation of jaundice at MacKay Children's Hospital were reviewed, along with 42 cases reported in the literature since 1990. Results The median age of the 12 patients was 1.85 years (range: 3 months–4 years), and 66.6% were male. All of the patients had elevated liver function at presentation, 50% had hydrops of the gallbladder, and almost 60% had gastrointestinal symptoms and signs. Complete KD was evident in 11 of the 12 patients (91.7%), and two patients (16.7%) had recurrent episodes. All of the patients received intravenous immunoglobulin (IVIG); however, one-third were refractory to treatment. Corticosteroids were used in five (41.7%) of the patients. Three (25%) of the patients had shock, and seven (58.3%) had coronary artery abnormalities, of whom one (8.3%) had persistent coronary artery aneurysm and the others recovered. A review of the 42 cases in the literature showed that the children with a jaundice-predominant presentation of KD had high rates of IVIG-refractory disease (25%), coronary artery abnormalities (25%), shock (13.2%), and corticosteroid treatment (24.2%). Conclusions Children with KD presenting with a jaundice-predominant manifestation are at a higher risk of IVIG-refractory disease, coronary artery abnormalities, and more recurrent episodes. Physicians should be aware of the risk of shock in this population.